2022
DOI: 10.1002/smi.3213
|View full text |Cite
|
Sign up to set email alerts
|

Is daily‐life stress reactivity a measure of stress recovery? An investigation of laboratory and daily‐life stress

Abstract: Typical measures of laboratory reactivity (i.e. difference between control and stress) and recovery (i.e. difference between stress and post‐stress) were compared with a conventional measure of daily‐life reactivity, best known as event‐related stress. Fifty‐three healthy individuals between 19 and 35 years of age took part in a laboratory session where stress was induced using the repeated Montreal Imaging Stress Task and 8 days of experience sampling method. Measures of negative affect, heart rate (HR), HR v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 77 publications
1
3
0
Order By: Relevance
“…It’s important to emphasized caution when interpreting these results. While our findings are consistent with previous studies that have employed similar procedures, its crucial to acknowledge the existence of studies that have failed to found a relationship between laboratory reactivity measures and those observed in everyday life ( Gerin et al, 1998 ; Baucom et al, 2018 ; De Calheiros Velozo et al, 2023 ). This potential disparity could impact the external validity of our current study.…”
Section: Discussionsupporting
confidence: 92%
“…It’s important to emphasized caution when interpreting these results. While our findings are consistent with previous studies that have employed similar procedures, its crucial to acknowledge the existence of studies that have failed to found a relationship between laboratory reactivity measures and those observed in everyday life ( Gerin et al, 1998 ; Baucom et al, 2018 ; De Calheiros Velozo et al, 2023 ). This potential disparity could impact the external validity of our current study.…”
Section: Discussionsupporting
confidence: 92%
“…Ethics approval was granted by the Sociaal-Maatschappelijke Etische Commissie of Katholieke Universitei Leuven (G-2018 09 1339) [ 24 ]. Informed consents were obtained from the participants.…”
Section: Methodsmentioning
confidence: 99%
“…This study included 45 healthy adult participants from Leuven, Belgium [ 24 ]. The average age of the participants was 24.5 (SD 3) years and ranged from 19 to 35 years.…”
Section: Methodsmentioning
confidence: 99%
“…Stress is a common experience in everyday life, triggering the release of stress hormones, which increase sweating, breathing, heart rate, and blood pressure as the body responds to perceived stressors (Zawadzki et al, 2019). While these reactions may be helpful in the short term, long-term stress can be detrimental (De Calheiros Velozo et al, 2023).…”
Section: Introductionmentioning
confidence: 99%